2011
DOI: 10.1007/s00216-010-4607-6
|View full text |Cite
|
Sign up to set email alerts
|

An analytical method for the simultaneous trace determination of acidic pharmaceuticals and phenolic endocrine disrupting chemicals in wastewater and sewage sludge by gas chromatography-mass spectrometry

Abstract: This article presents an analytical method based on solid-phase extraction (SPE) and gas chromatography coupled with mass spectrometry for the simultaneous determination of the most frequently used acidic pharmaceutical residues, ibuprofen, diclofenac, naproxen and ketoprofen (KFN), and phenolic endocrine disruptors, bisphenol (BPA), triclosan (TCS), nonylphenol, nonylphenol monoethoxylate and nonylphenol diethoxylate, in wastewater and sewage sludge samples. In the first phase of the study, each compound has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(47 citation statements)
references
References 41 publications
1
42
0
4
Order By: Relevance
“…As shown in Table 2.2, LODs ranged from 0.5 to 3.6 ng g -1 and LOQs from 1.8 to 12.1 ng g -1 , being amitriptyline the compound with the highest limit, since it is the one that presents the quantifier MRM with lowest abundance. The LODs obtained with the proposed method are in the same range or lower than those reported by other authors in the analysis of pharmaceutical compounds in biosolids (Dobor et al, 2010;Martín et al, 2010;Peysson and Vulliet, 2013;Radjenovic et al, 2009a;Samaras et al, 2011). …”
Section: Limits Of Detection (Lod) and Quantification (Loq) Ten Replsupporting
confidence: 71%
See 4 more Smart Citations
“…As shown in Table 2.2, LODs ranged from 0.5 to 3.6 ng g -1 and LOQs from 1.8 to 12.1 ng g -1 , being amitriptyline the compound with the highest limit, since it is the one that presents the quantifier MRM with lowest abundance. The LODs obtained with the proposed method are in the same range or lower than those reported by other authors in the analysis of pharmaceutical compounds in biosolids (Dobor et al, 2010;Martín et al, 2010;Peysson and Vulliet, 2013;Radjenovic et al, 2009a;Samaras et al, 2011). …”
Section: Limits Of Detection (Lod) and Quantification (Loq) Ten Replsupporting
confidence: 71%
“…In our study, we did not find residues of ketoprofen in any of the samples analyzed and naproxen was only found in three samples at low concentrations, from 12 to 23 ng g -1 (Jelic et al, 2011) performed the monitoring of pharmaceuticals in three conventional WWTPs over a period of two years and no residues of both NSAIDs were detected in any of the samples analyzed concluding that these compounds do not accumulate in sludge. Ketoprofen was not detected or quantified in sewage sludge from WWTPs in Athens (Greece) (Samaras et al, 2011) and Seville (Spain) (Martín et al, 2010), The anti-epileptic drug carbamazepine was not found in any of the samples at levels above LOD. Carbamazepine has a very low removal regardless of the treatment applied and does not adsorb onto the sludge (Jelic et al, 2011;Radjenovic et al, 2009b) although it has been found in sludge from different locations (Nieto et al, 2007(Nieto et al, , 2010aRadjenovic et al, 2009a).…”
Section: Figure 23 Gc-ms/ms Chromatograms Of the Pharmaceuticals Foumentioning
confidence: 94%
See 3 more Smart Citations